LANDASAN FILSAFAT SEBAGAI PENGEMBANGAN KURIKULUM: ANTARA IDEALISME, REALISME, DAN PRAGMATISME DALAM PENDIDIKAN - Tiara Alia (ADISAM PUBLISHER, 2026)
Islamic Religious Education (PAI) curriculum development requires a strong philosophical foundation to ensure that learning objectives are achieved effectively and meaningfully. This study discusses three main philosophical foundations, namely idealism, realism, and pragmatism, in the development of the PAI curriculum. Idealism emphasizes the formation of spiritual values and noble character as the main goal of education. Realism focuses on linking learning materials with real-life experiences and social contexts of students. Pragmatism highlights the usefulness and practical application of knowledge in everyday life. These three approaches are analyzed as complementary foundations that can strengthen the quality of Islamic education curriculum development. The study shows that an integrative approach among idealism, realism, and pragmatism is necessary to create a balanced and relevant PAI curriculum in responding to modern educational challenges.